Homeopathic Remedies for Management of Hypothyroidism: A Comprehensive Review (Homoeopathy for All, 2025)
Background: Hypothyroidism is a common  endocrine disease in the world,  which is characterized by decreased  thyroid hormone formation and  secretion, leading to extreme  fatigue, weight gain, cold  intolerance, depression, loss of  appetite, dryness, hair fall, female  problems like menstrual cycle,  infertility, and various metabolic  problems. Modern medical  treatment with levothyroxine with  side effects. Homeopathic System,  a holistic and individualized system  of homeopathic medicine, has  a significant effect in managing  hypothyroidism. Aim and Objective: This Comprehensive Review aims  to evaluate and synthesize clinical  evidence on the effectiveness  of homeopathic medicine in the  management of hypothyroidism  and subclinical hypothyroidism.  The objective is to assess the  significant impact of individualized  and constitutional homeopathic  medicine on thyroid function,  primarily improving TSH levels and  associated signs and symptoms. Methodology: A Comprehensive literature review  search was conducted using online  databases such as PubMed, Scopus,  and Google Scholar for articles  published between January 2020 and  December 2024. Keywords included  "hypothyroidism," "homeopathic  treatment," "homeopathy," and  "homeopathic management." Out  of 50 retrieved articles, six met the  inclusion criteria.  Results:Out of 50 retrieved articles,  six met the inclusion criteria  in the Comprehensive Review.  The Comprehensive Review of  studies consistently demonstrated  significant improvements in TSH  value, Zulewski’s clinical scores,  and patient-reported outcomes after  homeopathic treatment.  Conclusion: The findings of this Comprehensive  Review suggest that individual  homeopathic medicines may  have promising benefits in the  management of signs and symptoms  of hypothyroidism.
Keywords: Hypothyroidism; Homeopathic Treatment; Homeopathy; Review